Pleural Effusion Identified by Point of Care Ultrasound (POCUS) in Septic Shock: Impact on Clinical Outcomes - Erick Joel Rendón-Ramirez; Andrés Mauricio Morales-García; Adrián Rendón-Pérez; Homero Nañez-Terreros; Ricardo César Solis; Alexandra Daniela Magaña-García; Samantha Medrano-Juárez; José Francisco Caloca-Estrada; Roberto Mercado-Longoria; Jorge Eduardo Leija-Herrera; José M Porcel (POCUS Journal, 2024)
Aim: To analyze the association between pleural effusion detected by chest point of care ultrasound (POCUS) and clinical outcomes in patients with septic shock admitted to an intensive care unit (ICU). Material and methods: A prospective evaluation of ICU patients with septic shock in whom chest POCUS was performed during the first 24 hours of diagnosis to identify the presence and characteristics of pleural effusion. Results: Of 45 patients with septic shock, 17 (38%) had pleural effusion. Mortality (13 vs 17 patients, p=0.44), as well as length of stay in ICU (11.0 vs 6.5 days, p=0.161) were similar among groups. However, there was a significant difference in the modified Nutrition Risk in Critically Ill (mNUTRIC) score between the pleural effusion (5.82±1.13) and non-pleural effusion groups (4.00±2.39, p=0.001). In addition, patients with pleural effusion required more days on mechanical ventilation than those without pleural effusion (10 vs 7, p=0.04). A subgroup analysis of chest POCUS characteristics between surviving and non-surviving patients with pleural effusion identified a higher median size of pleural effusion in the non-surviving group (3±2.16 cm vs 1.9±0.6, p=0.01). Conclusion: Pleural effusion in patients with septic shock is associated with high mNUTRIC scores and more days on mechanical ventilation. The larger the pleural effusion, the lower the survival rate.